2016
DOI: 10.1136/bmjopen-2016-012116
|View full text |Cite
|
Sign up to set email alerts
|

Using digital notifications to improve attendance in clinic: systematic review and meta-analysis

Abstract: ObjectivesAssess the impact of text-based electronic notifications on improving clinic attendance, in relation to study quality (according to risk of bias), and to assess simple ways in which notifications can be optimised (ie, impact of multiple notifications).DesignSystematic review, study quality appraisal assessing risk of bias, data synthesised in meta-analyses.Data sourcesMEDLINE, EMBASE, PsycINFO, Web of Science and Cochrane Database of Systematic Reviews (01.01.05 until 25.4.15). A systematic search to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 37 publications
(11 reference statements)
4
63
0
Order By: Relevance
“…Based on our pilot survey, where 33.8% of parents reported to have forgotten their scheduled visit, the text messages could serve as a valuable prompt for keeping the scheduled appointment. This is consistent with previous literature demonstrating the utility of text message appointment reminders on different patient populations [3, 4]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on our pilot survey, where 33.8% of parents reported to have forgotten their scheduled visit, the text messages could serve as a valuable prompt for keeping the scheduled appointment. This is consistent with previous literature demonstrating the utility of text message appointment reminders on different patient populations [3, 4]. …”
Section: Discussionsupporting
confidence: 93%
“…A recent BMJ article published in 2016 also showed that text-based electronic notifications improved adherence [3]. However, the studies included in these reviews were heterogeneous, encompassing different interests.…”
Section: Introductionmentioning
confidence: 99%
“…However, drivers of the decreased donation rate between the main trial and the extension study could not be established given the study design. 29 Although participants were not informed of their randomly allocated group in the extension study, individuals returning to routine reminders might have noticed the change and potentially be influenced by the active reminders from the main trial.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research conducted in the form of RCTs showed that the text message approach could be effective. These studies were done in both the medical world (Taylor et al 2012) (Youssef et al 2014) (Robotham et al 2016) and with defendants when it came to changing their behaviour in fine payments (Haynes et al 2013). This fine payment trial in particular demonstrates that defendants can be influenced by such an approach.…”
Section: Results In Context Of Previous Researchmentioning
confidence: 99%